Football sentiment and stock market returns: Evidence from a frontier market - Trương, Quang Thái (Science Direct, 2022)
This study examines the effect of investor sentiment on the Vietnamese stock market. Using the results of international football matches as exogenous shocks on investor sentiment, and information from two major stock exchanges, we document a link between investor sentiment and stock market returns. In particular, we find a decline in market returns on the subsequent trading days after game losses. Moreover, the effect of investor sentiment on stock market returns is more pronounced between 2015 and 2020 during which football fans exhibited a stronger affection and attention to their teams. The results further depict that the impact of investor sentiment on stock market returns is only significant for small-cap stocks, and when more important tournaments are played.